Molecular composition and ultrastructure of the caveolar coat complex. - Alexander Ludwig (Public Library of Science (PLoS), 2013)
Caveolae are an abundant feature of the plasma membrane of many mammalian cell types, and have key roles in mechano-transduction, metabolic regulation, and vascular permeability. Caveolin and cavin proteins, as well as EHD2 and pacsin 2, are all present in caveolae. How these proteins assemble to form a protein interaction network for caveolar morphogenesis is not known. Using in vivo crosslinking, velocity gradient centrifugation, immuno-isolation, and tandem mass spectrometry, we determine that cavins and caveolins assemble into a homogenous 80S complex, which we term the caveolar coat complex. There are no further abundant components within this complex, and the complex excludes EHD2 and pacsin 2. Cavin 1 forms trimers and interacts with caveolin 1 with a molar ratio of about 1∶4. Cavins 2 and 3 compete for binding sites within the overall coat complex, and form distinct subcomplexes with cavin 1. The core interactions between caveolin 1 and cavin 1 are independent of cavin 2, cavin 3, and EHD2 expression, and the cavins themselves can still interact in the absence of caveolin 1. Using immuno-electron microscopy as well as a recently developed protein tag for electron microscopy (MiniSOG), we demonstrate that caveolar coat complexes form a distinct coat all around the caveolar bulb. In contrast, and consistent with our biochemical data, EHD2 defines a different domain at the caveolar neck. 3D electron tomograms of the caveolar coat, labeled using cavin-MiniSOG, show that the caveolar coat is composed of repeating units of a unitary caveolar coat complex.